Political Ideology in Consumer Resistance: Analyzing Far-Right Opposition to Multicultural Marketing. Issue 4 (October 2020) - Ulver, Sofia; Laurell, Christofer
Political ideologies of the far-right are gaining ground in world politics and culture, not least by way of market forces. It has therefore become urgent to understand how these ideologies manifest themselves in the fields of marketing and consumption at a sociocultural level. The authors explore the discursive efforts in far-right consumer resistance to advance a political agenda through protests directed at brands' multicultural advertising and analyze how these consumers conceptualize their adversaries in the marketplace. In contrast to previous framings of adversaries identified in consumer research, where resistance is typically anticapitalist and directed toward firms' unethical conduct or the exploitation by the global market economy per se, the authors find that the following discursive themes stand out in the far-right consumer resistance: the emphasis on the state as main antagonist, the indifference to capitalism as a potential adversary, and overt contestation of liberal ethics. The article concludes with a discussion of research contributions as well as the public policy and marketing implications in light of a growing far-right consumer culture.